Embodied Displays of “Doing Thinking.” Epistemic and Interactive Functions of Thinking Displays in Children's Argumentative Activities - Heller, Vivien (Frontiers in Psychology, 2021)
This study investigates moments in which one participant in an interaction embodies that he is ‘doing thinking’, a display that is commonly referred to as “thinking face”. From an interactional perspective, it is assumed that embodied displays of ‘doing thinking’ are a recurring social practice and serve interactive functions. While previous studies have examined thinking faces primarily in word searches and within narrative activities, the present study focuses on argumentative activities, in which children engage in processes of joint decision-making. It has two interrelated aims. The first aim is to describe how multiple modalities – beyond the face – are temporally coordinated to create multimodal gestalts of ‘doing thinking’. It is shown that thinking displays not only involve dynamic introspective gaze but also stylized bodily postures. The second aim is to generate knowledge about the functions of thinking displays in children’s argumentative activities. The analysis describes how both speakers and recipients use thinking displays in different turn positions and align them with verbal talk or silence. The data for this study comprise video recordings of decision-making processes in groups of older children. Drawing on a multimodal approach to situated interaction, it will be proposed that embodied displays of ‘doing thinking’ provide a resource to shape the interactive process. In addition, they enable participants to mark their epistemic stance and to create epistemic ecologies for collaborative reasoning. By investigating thinking displays in a particular conversational activity, the study sheds light on the diversity and context-sensitive functionality of thinking displays. It also contributes to recent research on children’s collaborative reasoning as an embodied discursive practice.